Language characteristics and tactics of naming Facebook accounts of Mahasarakham University students - Tueanjit Burana; Penprapa Singsawat (Journal of Humanities and Social Sciences Mahasarakham University, 2021)
The purpose of this article is to study the characteristics of the language and the tactics of naming Facebook user accounts of Mahasarakham University students by using a research methodology, the document together with the data storage from the questionnaires. The study selected 400 names of Mahasarakham University students’ username, divided into 200 males and 200 females. The study indicated that Language characteristics in naming a Facebook user account used 1-11 syllables. The most common was the 5 syllables. The alphabets used to name user accounts on Facebook were from two languages, Thai and English. The most common use of punctuation marks was in English where three types of punctuation were used, including single quotation marks, period, and hyphen. The most common was a single quotation mark. The results of the strategy for naming user accounts on Facebook. revealed 6 ways based on the names of living things, non-living things, symptoms, characteristics and etc. The most common was how to nameFacebook account in the name meaning the structure used to name the user account on Facebook found 2 types of structure which are single structure and mixed structure the most common are single structures. The study shows that for students at Mahasarakham University students the naming of accounts is likely to be outstanding and particular. Generally the account name is a name that shows the identity of the person.